Acacia gums new fractions and sparkling base wines: How their biochemical and structural properties impact foamability?. (30th August 2021) - Apolinar-Valiente, Rafael; Salmon, Thomas; Williams, Pascale; Nigen, Michaël; Sanchez, Christian; Doco, Thierry; Marchal, Richard
Highlights: The shaking test is a valid and simple method to measure foamability of base wines. Foamability is linked to the Ion Exclusion Chromatography (IEC) fractions features. High molar mass protein-rich fractions improve the foamability of base wines. F1 fractions always increase the significant maximal differentials of foam height. The effect of fraction addition on foam depends on base wine properties. Abstract: Foam is the first attribute observed when sparkling wine is served. Bentonite is essentially used to flocculate particles in sparkling base wines but can impair their foamability. Gums from Acacia senegal and Acacia seyal improved the foamability of different bentonite-treated base wines. Our main goal was to see how the supplementation with new fractions separated from Acacia gums by Ion Exchange Chromatography affected foamability of sparkling base wines, deepening the relation between foam behavior and characteristics of wine and gums. High molar mass fractions increased the maximal foam height and the foam height during the stability period in, respectively, 11 out and 8 out of 16 cases (69% and 50%, respectively). The properties of the supplementing gums fractions obtained by IEC and, although to a minor extent, the wine characteristics, affected positively and/or negatively the foam behavior. Wine foamability also depended on the relationship between wine and gums fractions properties.